Synthesis, Characterization and Electronic Structure of Dirhenadehyro[12]annulene Complexes. Issue 1 (13th December 2018) - Zheng, Shaohui; Chu, Zhenwei; Lee, Ka‐Ho; Lin, Qin; Li, Yucen; He, Guomei; Chen, Jiangxi; Jia, Guochen
Abstract: Treatment of the SiMe3 ‐protected dichloro‐rhenium carbyne complexes Re{≡CCH=C(R)C≡CSiMe3 }Cl2 (PMe2 Ph)3 (R = CMe3, 1‐adamantyl) with CsF in methanol directly afforded the 12‐membered metallacycles {ReCl(PMe2 Ph)3 }2 {≡CCH=C(R)C≡C−}2 . The electronic structure of the metallacycle was investigated by density functional calculations. The UV‐vis spectrum of the metallacycle shows a red‐shifted band compared to that of the starting dichlorocarbyne complex. Treatment of {ReCl(PMe2 Ph)3 }2 {≡CCH=C(CMe3 )C≡C−}2 with HCl produced the dichloro‐rhenium carbyne complex Re{≡CCH=C(CMe3 )C≡CH}Cl2 (PMe2 Ph)3, which is consistent with the electronic structure of the 12‐membered metallacycles. Abstract : Dirhenadehyro[12]annulenes were directly produced from the SiMe3 ‐protected dichloro‐rhenium carbyne complexes Re{≡CCH=C(R)C=CSiMe3 }Cl2 (PMe2 Ph)3 (R = CMe3, 1‐adamantyl) by treatment with CsF in methanol (see scheme). The UV‐vis spectrum of the 12‐membered metallacycle display a red‐shifted band compared with that of the starting dichlorocarbyne complex.